Research on an optimised encryption algorithm for network information security communication. (9th November 2022) - Li, Ju
At present, one of the commonly used encryption algorithms is the block cipher AES method, while in the design, we often only consider the bounded attack opponent, but in the face of the needs of the development of artificial intelligence, it is difficult to meet the secure communication of network information. This time, an optimised and improved GANs encryption algorithm based on neural network is proposed. The encryption algorithm can improve the objective function and learning model, so as to achieve better algorithm security performance. Through simulation analysis, it can also be seen that with the increase of training times, the neural network training effect of Bob, Alice and Eve is better. The proposed optimisation algorithm can realise face generation in the case of non-artificial knowledge, which has significant advantages compared with the traditional encryption algorithm.